1994
DOI: 10.1002/1097-0142(19940915)74:6<1693::aid-cncr2820740609>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Expression of epidermal growth factor receptor and proliferating cell nuclear antigen predicts response of esophageal squamous cell carcinoma to chemoradiotherapy

Abstract: Background. Multimodality therapy with chemotherapy and radiotherapy followed by surgery may improve survival in patients with esophageal squamous cell carcinoma compared with each of the individual treatment options. Histologic assessment of resected tumors after chemoradiotherapy shows that some patients have a complete response with no residual tumor, whereas other patients derive no benefit. The ability to predict response to chemoradiotherapy would allow treatment to be planned accordingly. Methods. Expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
67
0
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(72 citation statements)
references
References 18 publications
4
67
0
1
Order By: Relevance
“…Patients who had tumors that expressed EGFR had shorter disease-free and overall survival compared with patients who had EGFR-negative tumors, but EGFR expression was not an independent prognostic indicator for either parameter in multivariate analysis. Although there have been several studies of EGFR expression in esophageal squamous cell carcinomas, 21,[25][26][27][35][36][37][38] studies of the role of EGFR in esophageal adenocarcinomas have been limited. 28,29,39 Similar to our studies, the majority of the esophageal adenocarcinomas in previous studies were from the lower one-third of the esophagus or from the GEJ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who had tumors that expressed EGFR had shorter disease-free and overall survival compared with patients who had EGFR-negative tumors, but EGFR expression was not an independent prognostic indicator for either parameter in multivariate analysis. Although there have been several studies of EGFR expression in esophageal squamous cell carcinomas, 21,[25][26][27][35][36][37][38] studies of the role of EGFR in esophageal adenocarcinomas have been limited. 28,29,39 Similar to our studies, the majority of the esophageal adenocarcinomas in previous studies were from the lower one-third of the esophagus or from the GEJ.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with head and neck, ovarian, cervical, bladder, and esophageal squamous cell carcinomas, EGFR expression is a strong prognostic indicator that correlates with both higher recurrence rates and shorter survival. [11][12][13]17,21,22,[25][26][27][35][36][37][38] In the current study, we demonstrated that EGFR expression in esophageal adenocarcinoma correlates with outcome in patients who are treated with esophagectomy alone. Our data showed that EGFR expression is correlated strongly with poor overall and disease-free survival in univariate analyses with a trend toward correlation in multivariate analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, whereas some studies have indicated that p53 gene mutation and/or p53 protein accumulation in tumour cells may be significantly associated with resistance to multimodal therapy and/or poor survival (Seitz et al, 1995;Ribeiro et al, 1998;Sarbia et al, 1998;Krasna et al, 1999;Gibson et al, 2003), others have not found such a correlation (Soontrapornchai et al, 1999;Ito et al, 2001;Shimada et al, 2002;Pühringer-Oppermann et al, 2006). With regard to EGFR, two studies indicated that tumours with strong EGFR expression show a relatively poor response to chemoradiotherapy (Hickey et al, 1994;Gibson et al, 2003), whereas another study did not find such a correlation (Miyazono et al, 2004). Moreover, in one of the two positive studies (Gibson et al, 2003), EGFR was found to have predictive value in oesophageal adenocarcinoma, but not in squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…PCNA has been considered to be a useful marker of proliferating activity in some tumours (Hall et al, 1990;Jain et al, 1991;AlSheneber et al, 1993), including oesophageal SCC (Hickey et al, 1994;Kinugasa et al, 1996), and appears at the late G1/S boundary in the cell cycle. Nagel and Vallee (1995) reported that the level of MT during the mitotic cell cycle of human colon cancer cells reached its maximum near the G1/S boundary of the cell cycle, around the onset of DNA synthesis, raising a physiological role for MT in cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we have attempted to correlate the expression of MT with proliferating cell nuclear antigen (PCNA) expression, since in gastrointestinal tumours significant correlation have been noticed between proliferative activity and metastatic potential (Hall et al, 1990;Jain et al, 1991;Al-Sheneber et al, 1993;Hickey et al, 1994;Kinugasa et al, 1996).…”
mentioning
confidence: 99%